Approximation of stochastic invariant manifolds : stochastic manifolds for nonlinear SPDEs I /: stochastic manifolds for nonlinear SPDEs I. ([2014]) - Chekroun, Mickaël D; Liu, Honghu; Wang, Shouhong
No abstract available